2014
DOI: 10.5505/tjtes.2014.12244
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of ClinOleic against post-surgical adhesions

Abstract: BACKGROUND: Although the English-language literature is full of studies about post-surgical adhesions, no definitive method has yet been identified to prevent them. The goal of this study was to investigate the effect of ClinOleic on reducing post-surgical adhesion formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Additionaly the anti-inflammatory effect of fatty acids, Jiang et al reported that γ-tocopherol inhibits proinflammatory PGE2 and LTB4, decreases TNF-alpha, and γ-tocopherol shows antiinflammatory effect [7][8][9][10][11]22]. Giant cells are seen in granulamatous inflammation that is different patern of chronic inflammatory reaction and generally occurs due to foreign bodies [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionaly the anti-inflammatory effect of fatty acids, Jiang et al reported that γ-tocopherol inhibits proinflammatory PGE2 and LTB4, decreases TNF-alpha, and γ-tocopherol shows antiinflammatory effect [7][8][9][10][11]22]. Giant cells are seen in granulamatous inflammation that is different patern of chronic inflammatory reaction and generally occurs due to foreign bodies [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Argan oil reduced adhesion formation with its liquid form like as soybean oil, olive oil, omega 3 fatty acids [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopy has fewer potential complications than laparotomy [20], such as adhesions, intestinal obstruction, infertility, and chronic pelvic pain [2,9]. CO 2 insufflation for good visualization during surgery causes hypoxic and splenic ischemia and triggers peritoneal adhesion [9,21].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the mechanism of adhesion formation, fibrinolysis and extracellular matrix remodeling, including cell proliferation, migration, differentiation, angiogenesis, and apoptosis, are critical for the regulation of the adhesive process as controlling inflammation at initial stages (7,13,14).…”
Section: Discussionmentioning
confidence: 99%